Effect of vegetation on outdoor thermal comfort in hot arid regions, a lesson of sustainability from the traditional Ksar of Ain Madhi, Algeria - Dohssi, Khadidja; Djaghrouri, Djamila; Benabbas, M. (Technium Social Sciences Journal, 2022)
Regarding the important effects of thermal comfort on residents, especially in hot regions, our study aimed to investigate and determine the influence of vegetation on the external thermal comfort conditions in the Algerian Sahara. In our work, we examine the determining factors of thermal comfort at three points in the Ksar of Ain Madhi by coupling in-situ measurement and simulation with the Rayman 1.2 software. The measured parameters are air temperature (Ta), relative humidity (HR). The simulated parameters are global actual radiation (Gact), direct actual radiation (Sact), surface temperature (Ts), mean radiant temperature (MRT), predicted mean vote (PMV) and physiological equivalent temperature (PET), this work is such a lesson of sustainability that we should take into account for future urban development especially in hot arid regions.